On Tuza's conjecture in even co-chain graphs - Chahua, Luis; Gutiérrez, Juan (Anais do Encontro de Teoria da Computação (ETC); 2022: Anais do VII Encontro de Teoria da ComputaçãoDO - 10.5753/etc.2022.223185, 2022)
In 1981, Tuza conjectured that the cardinality of a minimum set of edges that intersects every triangle of a graph is at most twice the cardinality of a maximum set of edge-disjoint triangles. This conjecture has been proved for several important graph classes, as planar graphs, tripartite graphs, among others. However, it remains open on other important classes of graphs, as chordal graphs. Furthermore, it remains open for main subclasses of chordal graphs, as split graphs and interval graphs. In this paper, we show that Tuza’s conjecture is valid for even co-chain graphs, a known subclass of interval graphs.